Ferguson as a distal crisis - Jurek, Alicia L. (Criminology & public policy, 2022)
We explore how a widely publicized crisis in another jurisdiction, a distal crisis, affects police agencies that were far removed from the crisis. Using data from a two-wave, panel-design survey of 411 police chiefs in Texas, we investigate how the events occurring in Ferguson, Missouri during 2014 changed chiefs’ perceptions of their institutional environmental sectors. Although distant from Ferguson, in the immediate aftermath chiefs rated two (local and national media) of eight (federal, state, and local law enforcement organizations as well as elected officials, police employee associations, local emergency medical organizations, and local advocacy groups) institutional sectors (including local and national media) as less impactful or legitimate.